Value chain and multi-crop baseline of the Transforming Agrifood Systems in West and Central Africa Initiative (TAFS-WCA): A case of Burundi - Arouna, A.; Yergo, W.G.; Aboudou, R.; Ouedraogo, M.; Abdoulaye, T. (Africa Rice Center, 2023)
This report presents the results of the baseline survey of the Transforming Agrifood Systems in West and Central Africa initiative (TAFS-WCA) in Burundi. Six regions of Burundi were surveyed. Data were collected using a smart tablet with the CSPro application. A total of 572 actors in agricultural production and value chain were surveyed during the baseline data collection in Burundi. These are mainly rice, beans, cassava, banana and sweet potato producers, inputs dealer, traders, processors and service providers. All data analyses were carried out with the STATA 16 software. Out of the surveyed population, 41.61% (238) are rice producers, 10.49% (60) bean producers, 10.49% (60) cassava producers, 11.01% (63) sweet potato producers, 11.66% (99) banana producers, 12.76% (73) traders, 2.27% (13) processors and 0.70% (4) service providers. The average age of actors is 43 years old and ranges from 18 to 79 years old, and the average household size is 6 persons. About 67% of actors are male and 88% are married. In addition, 77% of the actors have received formal education and 84% have crop production has main activity. Moreover, 76 % of producers produce during the rainy season, 9% during dry season while 15% in both seasons. With regard to climate change information’s, about 9% of producers have access to forecasts of extreme climatic events (drought, flood, strong wind, etc.) and 8% to information on seasonal forecasts (weather for the following 2-3 months). In relation to food security and the poverty index, preliminary results show that the vast majority of actors have an acceptable level of dietary diversity, meal frequency and nutritional importance of the food groups consumed; and according to the poverty index, the rate of poor actors is 56%